Penguatan Karakter Cinta Damai Bagi Generasi Muda dalam Mewujudkan Lingkungan Aman dan Nyaman di Desa Gogik - Tutik Wijayanti; Masrukhi Masrukhi; Hendri Irawan; Suyahmo Suyahmo (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Youth play a strategic role in maintaining social harmony and creating a safe and comfortable environment. However, various social challenges such as rising conflicts, a lack of awareness of peace values, and the negative influence of social media pose obstacles to building a peace-loving character. This community service aims to strengthen the character of peace-loving values among youth in Gogik Village, West Ungaran District, through interactive education and training. The service method involves mentoring and empowerment activities targeting the community through the local youth organization (Karang Taruna) by conducting training programs and digital campaigns. This initiative is expected to raise awareness and understanding among young people about peace values through training activities and digital outreach, helping them improve their knowledge of conflict management, effective communication, and the importance of creating a harmonious environment. Additionally, participants became more active in spreading messages of peace via social media. The significance of this community service lies in its contribution to reinforcing peace-loving character through educational approaches and digital technology, which can enhance youth awareness in preserving social stability. Therefore, synergy among government, communities, and educational institutions is essential to broaden the implementation of similar programs to build a more peaceful and tolerant society